Dampak Sosial Dan Kultural Pernikahan Terhadap Kualitas Hidup Lansia Dalam Dinamika Stigma Sosial Di Masyarakat Global: A Literature Review - Yance Hidayat; Jipri Suyanto (PT Nuansa Fajar Cemerlang, 2025)
Early marriage, despite many countries having legislated marriage age limits, still occurs and has significant long-term impacts on the quality of life of individuals, especially older adults who experience it. The social and cultural impacts of early marriage, such as educational inequality, economic hardship, and social stigma, worsen the quality of life of older people who have married young, leaving them isolated and lacking access to necessary services. In a global context, early marriage also affects the physical and mental health of older people, including reproductive health problems, economic dependency, and difficulty adapting to social change, which worsens their condition as they age. The aim of this study was to examine the social and cultural impact of early marriage on older people's quality of life, with a focus on the dynamics of social stigma in global society. This study used the PRISMA approach to conduct a systematic literature review on quality of life in older adults. Selected articles were screened using inclusion and exclusion criteria based on the PICOS framework, which included population, intervention, comparison, outcome, and study design. Literature searches were conducted in reputable databases such as PubMed, Google Scholar, and ScienceDirect, with restrictions on English-language studies published between 2019 and 2025. Studies that met the criteria were included in a narrative synthesis analysis, which identified trends, patterns, and gaps in research findings. The selection and synthesis process was conducted with transparency, ensuring that the research results were based on reliable evidence. Research on the quality of life of older adults shows that various social, cultural, and activity factors influence their well-being. One study found that most older adults had a high quality of life, with traditional values of marriage having a significant effect on their well-being. Marital status also played an important role, with married older people showing better quality of life, especially in social relationships and psychological health. Another study showed the quality of life of older people in social care centers, where age and marital status influenced differences in quality of life, although gender, education, and length of stay did not have a significant effect. Meanwhile, older people's participation in customized cultural activities can improve their quality of life, with the involved group showing significant improvements compared to the control group. Social factors such as culture, marital status, and participation in cultural activities have a major influence on the quality of life of older adults. Local cultural values and social support can improve the well-being of older people, while cultural activities integrated into care also have a positive impact. Programs that support cultural values and meet the social needs of older people are important for improving their quality of life. Cooperation between the government, social institutions and communities is needed to create a supportive environment for the elderly.